A New Proof of Diophantine Equation $\Bigg( \begin{matrix} n \\ 2 \end{matrix} \Bigg) = \Bigg( \begin{matrix} m \\ 4 \end{matrix} \Bigg)$ (Communications in Mathematical Research, 2021)
By using algebraic number theory and $p$-adic analysis method, we give a new and simple proof of Diophantine equation $\Bigg( \begin{matrix} n \\ 2  \end{matrix} \Bigg) = \Bigg( \begin{matrix} m \\ 4  \end{matrix} \Bigg)$.
Keywords: binomial Diophantine equation; fundamental unit; factorization; $p$-adic analysis method.